The Cellular RNA Helicase DDX1 Interacts with Coronavirus Nonstructural Protein 14 and Enhances Viral Replication - Xu, Linghui (American Society for Microbiology (ASM), 2010)
The involvement of host proteins in the replication and transcription of viral RNA is a poorly understood area for many RNA viruses. For coronaviruses, it was long speculated that replication of the giant RNA genome and transcription of multiple subgenomic mRNA species by a unique discontinuous transcription mechanism may require host cofactors. To search for such cellular proteins, yeast two-hybrid screening was carried out by using the nonstructural protein 14 (nsp14) from the coronavirus infectious bronchitis virus (IBV) as a bait protein, leading to the identification of DDX1, a cellular RNA helicase in the DExD/H helicase family, as a potential interacting partner. This interaction was subsequently confirmed by coimmunoprecipitation assays with cells coexpressing the two proteins and with IBV-infected cells. Furthermore, the endogenous DDX1 protein was found to be relocated from the nucleus to the cytoplasm in IBV-infected cells. In addition to its interaction with IBV nsp14, DDX1 could also interact with the nsp14 protein from severe acute respiratory syndrome coronavirus (SARS-CoV), suggesting that interaction with DDX1 may be a general feature of coronavirus nsp14. The interacting domains were mapped to the C-terminal region of DDX1 containing motifs V and VI and to the N-terminal portion of nsp14. Manipulation of DDX1 expression, either by small interfering RNA-induced knockdown or by overexpression of a mutant DDX1 protein, confirmed that this interaction may enhance IBV replication. This study reveals that DDX1 contributes to efficient coronavirus replication in cell culture.